Implementation Of The Meaning Of The Phrase “In Certain Circumstances And The Level Of Truth That Is Considered Sufficient According To The Head Of The Land Office” In Article 37 Paragraph (2) Of Government Regulation Number 24 Of 1997 On Land Registratio - Nuruddin, Nuruddin; Herlindah, Herlindah; Supriyadi, Supriyadi (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to examine and analyze the implementation of the meaning of the phrase